Psychosocial Factors and Academic Performance in Nursing Students - Pérez-Briones, Nancy Griselda (2025)
Purpose. To determine the influence of psychosocial factors on academic performance among nursing students of a technical school in Saltillo, Coahuila. Methodology. Quantitative research was conducted, using a descriptive correlational design. The study population consisted of 270 students; convenience sampling was applied, obtaining a sample of 139 participants who completed an online questionnaire. A sociodemographic data form, the Rosenberg Scale for self-esteem, the Goldberg Anxiety and Depression Scale, the Emotional Fati222gue Scale [ECE], the Fagerström Scale for tobacco consumption, and the CAGE Scale for alcohol consumption were used to measure the factors. Academic performance was assessed using the students’ average grade from the previous semester. To address the general objective, a multiple linear regression model was applied. Results. Significant associations were found between anxiety (rs = -.119, p<.01), depression (rs = -.210, p<.01), emotional exhaustion (rs = -.352, p<.01), and alcohol consumption (rs = -.319, p<.01) with academic performance. The model showed that anxiety (β = -.946, p <.05), depression (β = -1.711, p <.05), emotional exhaustion (β = -4.842, p <.05), and alcohol consumption (β = -2.519, p <.05) predicted 46% of academic performance in nursing students. Conclusion. The study revealed that most students exhibited anxiety, depression and emotional exhaustion, conditions that may have an impact on their physical, mental and social health. These findings highlight the need to address mental health among upper secondary students to improve their academic performance.